Patient outcomes in public sector hepatitis C treatment programmes: a retrospective cohort analysis across five low- and middle-income countries - Caroline E Boeke; Clement Adesigbin; Chukwuemeka Agwuocha; Atiek Anartati; Khin Sanda Aung; Gagandeep Singh Grover; Dang Ngo; Siddharth Sindhwani; Craig McClure; Christian B Ramers; Olayinka Adisa; Muhammad-Mujtaba Akanmu; et al. (BMJ Open)
Objectives Given limited data on factors associated with hepatitis C virus (HCV) treatment discontinuation and failure in low- and middle-income countries, we aimed to describe patient populations treated for HCV in five countries and identify patient groups that may need additional support.Design Retrospective cohort analysis using routinely collected data.Setting Public sector HCV treatment programmes in India (Punjab), Indonesia, Myanmar, Nigeria (Nasarawa) and Vietnam.Participants 104 957 patients who initiated treatment in 2016–2022 (89% from Punjab).Primary outcomes Treatment completion and cure.Results Patient characteristics and factors associated with outcomes varied across countries and facilities. Across all patients, median age was 40 years (IQR: 29–52), 30.6% were female, 7.0% reported a history of injecting drugs, 18.2% were cirrhotic and 4.9% were coinfected with HIV. 79.8% were prescribed sofosbuvir+daclastasvir. Of patients with adequate follow-up, 90.6% (89,551) completed treatment. 77.5% (69,426) of those who completed treatment also completed sustained virological testing at 12 weeks (SVR12), and of those, 92.6% (64 305) were cured. In multivariable-adjusted models, in most countries, significantly lower treatment completion was observed among patients on 24-week regimens (vs 12-week regimens) and those initiated in later years of the programme. In several countries, males, younger patients <20 years and certain groups of cirrhotic patients were less likely to complete treatment or be cured. In Punjab, treatment completion was also lower in those with a family history of HCV and people who inject drugs (PWID); in other countries, outcomes were comparable for PWID.Conclusion High proportions of patients completed treatment and were cured across patient groups and countries. SVR12 follow-up could be strengthened. Males, younger people and those with decompensated cirrhosis on longer regimens may require additional support to complete treatment and achieve cure. Adequate programme financing, minimal user fees and implementation of evidence-based policies will be critical to close gaps.